2011
DOI: 10.1007/s11427-011-4207-5
|View full text |Cite
|
Sign up to set email alerts
|

Physiological roles of NAADP-mediated Ca2+ signaling

Abstract: Nicotinic acid dinucleotide phosphate (NAADP) is unique amongst Ca 2+ mobilizing messengers in that its principal function is to mobilize Ca 2+ from acidic organelles. Early studies indicated that it was likely that NAADP activates a novel Ca 2+ release channel distinct from the well characterized Ca 2+ release channels on the (sarco)-endoplasmic reticulum (ER), inositol trisphosphate and ryanodine receptors. In this review, we discuss the emergence of a novel family of endolysosomal channels, the two-pore cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 81 publications
(78 reference statements)
0
28
0
Order By: Relevance
“…4 is a potent Ca 2ϩ -releasing messenger that has been shown to regulate many physiological processes encompassing fertilization, secretion, neurite outgrowth, and synaptic function (1)(2)(3)(4). Although molecular identification of the Ca 2ϩ channel(s) targeted by NAADP remained frustratingly elusive for many years, several lines of evidence have recently unmasked the two-pore channel (TPC) family of endolysosomal proteins as candidate NAADP receptors (5-7).…”
Section: Naadpmentioning
confidence: 99%
“…4 is a potent Ca 2ϩ -releasing messenger that has been shown to regulate many physiological processes encompassing fertilization, secretion, neurite outgrowth, and synaptic function (1)(2)(3)(4). Although molecular identification of the Ca 2ϩ channel(s) targeted by NAADP remained frustratingly elusive for many years, several lines of evidence have recently unmasked the two-pore channel (TPC) family of endolysosomal proteins as candidate NAADP receptors (5-7).…”
Section: Naadpmentioning
confidence: 99%
“…Cytosolic calcium can also increase in response to the second messenger nicotinic acid adenine dinucleotide phosphate (NAADP) (21-24). NAADP releases calcium from acidic endolysosomal stores (21)(22)(23)(25)(26)(27)(28) by activation of two-pore channels (29 -31). Since its discovery by Lee and colleagues (17,22) almost 20 years ago, the emerging consensus is that NAADP is a widespread messenger that plays physiological roles in many mammalian systems (6,21,23,24,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41).…”
mentioning
confidence: 99%
“…NAADP releases calcium from acidic endolysosomal stores (21)(22)(23)(25)(26)(27)(28) by activation of two-pore channels (29 -31). Since its discovery by Lee and colleagues (17,22) almost 20 years ago, the emerging consensus is that NAADP is a widespread messenger that plays physiological roles in many mammalian systems (6,21,23,24,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41).In airway smooth muscle contraction, both IP 3 and cyclic ADP-ribose and their signaling components have been reported and well characterized (3,5,6,8,12,13,34), but a role for NAADP in this muscle type has not been reported. One study did investigate a role for NAADP in tracheal smooth muscle but reported negative results (42).…”
mentioning
confidence: 99%
“…Recent studies indicate that NAADP acts upon a novel family of endo-lysosomal channels in animal cells termed two-pore channels (TPCs) [20,21]. Galione et al [22] then summarized the physiological roles of NAADPmediated Ca 2+ signalling. They provided a historical perspective on the research of TPCs, studies on which unveiled the physiological role of NAADP as an intracellular Ca 2+ mobilizing messenger.…”
mentioning
confidence: 99%